Macroeconomic Theory - McCafferty, Stephen (New York Happer and Row, Publishers, 1990)
The book offers first-year Ph.D. students and mathematically well prepared masters students in economics as introduction to graduate-level macroeconomic theory. The primary goal of the text is to provide students whose backgrounds and with intermediate under-graduate macroeconomics the necessary foundation for more advanced course work.
Keywords: Economics